An Ayurvedic Management of Epistaxis: A Case Study - Sheenam, V D; fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2021)
Epistaxis or nose bleeds is the commonest complain which can cause of life threatening. Its prevalence cannot be exactly known as most cases are self-limited and patients usually seek medical attention only when the problem is either recurrent or severe in nature, As per Ayurveda classics this condition can be correlated with Nasagat Raktpitta. Which is caused by vitiation of Pitta Dosha in Rakta Dhatu (blood). Objective of this case study was to observe the efficacy of Ayurvedic treatment in the management of Nasagat Raktpitta (epistaxis). Present study was conducted on 21-year-old male patient of epistaxis in the OPD of Shalakya tantra, NIA. Patient presented with the complaint of bleeding from the nose for 6 months. History and examinations lead to diagnosis epistaxis (Nasagat Raktpitta), so patient was treated with Durva Svarasa Nasya and Sarivadi vati orally. Remarkable result was observed in the form of improvement in chief completions of the patient.